Berbagai Elemen Yang Berdampak Pada Kepuasan Pelanggan - Darwati Setiyani (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This research discusses various elements that have a significant impact on customer satisfaction in the context of various industries. Through in-depth analysis of factors such as product quality, customer service, price, and user experience, this research aims to understand the complex relationship between these elements and customer satisfaction levels. The research methods used include surveys, interviews, and statistical data analysis to collect relevant information. The results of this research provide in-depth insight into the elements that have the most significant impact on customer satisfaction, providing a foundation for organizations to improve their strategies for creating more positive customer experiences.